2014
DOI: 10.9734/bjpr/2014/6359
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Antioxidant, Antihyperglycaemic and Antihyperlipidaemic Activities of Ethanol Extract of Lawsonia inermis Leaves

Abstract: Aim: This present study investigated the free radical scavenging activities, antihperglycaemic and antihyperlipidaemic activities of ethanol extract of Lawsonia inermis leaves. Study Design: Twenty male rats were randomly and evenly distributed into four groups, and were subsequently exposed to the following treatments for twenty-one days: Group I (Control): Normal saline; Group II: Untreated Diabetic control; Group III: Diabetic rats treated with glibenclamide (600mg/Kg. b.wt); Group IV: Diabetic rats treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 27 publications
2
8
0
Order By: Relevance
“…Moreover, other recent studies, using as Ojewunmi et al [34], using phenolic compounds extracts from Lawsonia inermis have reported a concentration of inhibition at 50% (of DPPH) with 49.22 μg/mL via an ethanolic extract of leaves. Similar work carried by Guha et al [35] and Enneb et al [36] reported concentrations of 32.87 μg/mL and 25.73 μg/mL, respectively, of methanolic extracts of this same species.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, other recent studies, using as Ojewunmi et al [34], using phenolic compounds extracts from Lawsonia inermis have reported a concentration of inhibition at 50% (of DPPH) with 49.22 μg/mL via an ethanolic extract of leaves. Similar work carried by Guha et al [35] and Enneb et al [36] reported concentrations of 32.87 μg/mL and 25.73 μg/mL, respectively, of methanolic extracts of this same species.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that any of these phytochemicals could be associated with the antihyperlidipemic effect of the plant. The antihyperlipidaemic effect might have resulted from decreased fatty acid concentration in the circulation and reduced cholesterol synthesis possibly due to the flavonoid constituents of the plant extract (Ojewunmi et al, 2014). The actual mechanism of action and the phytoconstituent responsible for the observed effects of the plant, however, needs to be investigated further.…”
Section: Resultsmentioning
confidence: 99%
“…The total flavonoid content was estimated by using the slightly modified colorimetric method originally described by Woisky and Salatin 49 and applicable for glycosylated or non-glycosylated flavonoids determination 50 . An aliquot (1.5 mL) of the extract was mixed with 3 mL of methanol, 0.2 mL of 10% aluminum chloride, 0.2 mL of 1 M potassium acetate, and 5.6 mL of distilled water.…”
Section: Methodsmentioning
confidence: 99%